Implementasi Nilai Dakwah dan Ekonomi Syariah Dalam Motif Batik IRD Walisongo - Indriya Rusmana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2020)
The art of batik wastra (cloth) has traveled a very long journey in part of the Indonesian cultural fabric, to modern designs or patterns that adorn clothing. Apart from being exclusive, batik is never really the same as the others, and in each of its many stories and philosophical values. Batik is a cultural achievement, world cultural heritage and Indonesia. As a characteristic of the people's economic wealth, batik is also constantly being preserved and developed. However, batik is one of the cultural heritages of the Indonesian nation's ancestors. Walisongo or Walisanga was known as the spreader of Islam in Java around the 17th century.These Guardians lived in three important areas of the north coast of Java Island, namely Surabaya-Gresik-Lamongan in East Java, Demak-Kudus-Muria in Central Java, and Cirebon in West Java. Not only were they known as propagators of Islam, Walisongo were intellectuals who became community reformers at their time. At that time, Walisongo introduced various forms of new civilizations, ranging from farming, commerce, health, culture, arts, society to government. For example, the Ampel Denta and Giri Islamic boarding schools were the two most important educational institutions at that time, starting from Giri, Islamic civilization developed throughout the eastern region of the archipelago. Batik IRD Walisongo has a